2016
DOI: 10.1016/j.jcrs.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in intraocular lens position and corneal curvature after cataract surgery and their effect on refraction

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
2
16
1
Order By: Relevance
“…A 0.03-mm shift in an intraocular lens translates into a 0.05-D refraction change. 16 The present study showed that photopic conditions induced a 0.04-mm increase in ACD-ICL and that accommodation induced a 0.05-mm decrease in ACD-ICL. This translates into 0.03- and 0.04-D refraction changes, respectively.…”
Section: Discussionsupporting
confidence: 58%
“…A 0.03-mm shift in an intraocular lens translates into a 0.05-D refraction change. 16 The present study showed that photopic conditions induced a 0.04-mm increase in ACD-ICL and that accommodation induced a 0.05-mm decrease in ACD-ICL. This translates into 0.03- and 0.04-D refraction changes, respectively.…”
Section: Discussionsupporting
confidence: 58%
“…Postoperative measurements were obtained 2 to 4 months after surgery. Long-term (1 day to 1 year) changes in refractive outcomes in single-piece IOLs (as the IOL of the present study) due to IOL position shifts have been reported to be of negligible clinical relevance 38 , 39 . Further analysis will be needed to potentially incorporate IOL postoperative shifts in other types of IOLs (e.g., multipiece IOLs).…”
Section: Discussionmentioning
confidence: 56%
“…It has been estimated that a 0.033 mm ± 0.060 (SD) anterior-posterior shift in lens position correlates to a 0.05 diopter change in lens power. 5 This patient's postoperative refractive error measured −1.0 D, while the estimated lens position changed only 0.01 mm in the anterior direction. Therefore, it is likely that change in lens position does not completely explain the patient's myopic shift.…”
Section: Discussionmentioning
confidence: 76%